The Synthesis of Metal-Free and Metalloporphyrazines Carrying 2-Ethoxytetrahydro-2H-Pyranthio Groups for Dye-Sensitized Solar Cell, Investigation of Spectroscopic and Photovoltaic Properties - Kilicarslan, Fatma Aytan; Erden, Ibrahim; Gurbuz, Osman; Erdogmus, Ali; Okutan, Mustafa (AMER SCIENTIFIC PUBLISHERS, 2016)
The synthesis, characterization and photovoltaic properties of symmetric octakis(2-ethoxytetrahydro-2H-pyranthio) porphyrazines complexes were reported. The experiments were performed on metal-free and metalloporphyrazines Mg (II), Co (II), Ni (II) and Zn (II). The new compounds have been characterized by elemental analysis, UV-vis, FTIR, H-1-NMR and mass spectra. The spectral properties such as electronic spectra and aggregation of metalloporphyrazines compounds were studied in chloroform. The photovoltaic cell efficiencies (PCE) of the devices were in the range of 2.14-5.40% under simulated AM 1,5 solar irradiation of 100 mW/cm(2), and the highest V-oc reached 1.27 V. Compared with the metal-free and metalloporphyrazines compounds based on DSSCs, the ZnPz based DSSCs exhibited significantly excellent photovoltaic activities under their radiation of visible light.
Keywords: Porphyrazines; Aggregation; Photovoltaic Cell Efficiency; ORGANIC-DYES; PHTHALOCYANINES; TIO2; PORPHYRAZINE; DERIVATIVES; PORPHYRINS; Energy & Fuels